Geoscience – Canada’s Profession:: A Review of Professional Geoscience in Canada, and the Development, Activities and Relationships of Geoscientists Canada - Bonham, Oliver (Geoscience Canada, 2010)
SUMMARY Part of the recognition by society of the reliance the public places on the services that geoscientists provide, is the move by governments to assure competence and achieve accountability through professional registration; and it is because of the complex and specialized nature of the work of geoscientists that authorities have entrusted the profession with the legal power to self-regulate. As with other professions in Canada, geoscience is regulated at the provincial/territorial level under statutes that establish the regulatory bodies, define scopes of practice for geoscientists and secure protected title for individuals who practice geo-science. Currently, geoscience is a regulated profession in 11 of Canada’s 13 provinces and territories. The practice of geoscience is not yet regulated in either Prince Edward Island or Yukon. Geoscientists Canada, the business name of the Canadian Council of Professional Geoscientists, was established as a focus for collective and collaborative work by the 10 regulatory bodies that govern geoscience practice in Canada. At the end of 2009, there were 8872 professional geologists registered in Canada. This paper reviews the context of the regulation of geo-science in Canada and reports on developments concerning the profession. It also provides an update of the work that has recently been completed, is underway and is planned, by Geoscientists Canada on behalf of the regulatory bodies and the profession as a whole, both at the national and international level.